2019
DOI: 10.1371/journal.pone.0222190
|View full text |Cite
|
Sign up to set email alerts
|

Myotendinous asymmetries derived from the prolonged practice of badminton in professional players

Abstract: BackgroundThe continued practice of a sport linked to the unilateral predominance of the dominant side can provoke chronic asymmetric adaptations in the myotendinous structure and mechanical properties. Objectives: The main purpose was to determine whether asymmetry between the preferred and non-preferred lower limb is present in the lower limb tendon structure, muscle architecture and stiffness values of professional badminton players.MethodsSixteen male professional badminton players (age = 24.1 ± 6.7 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
(108 reference statements)
0
18
0
4
Order By: Relevance
“…For example, thicker and wider Achilles and patellar tendons in the racket leg. 36 As the magnitude of asymmetry would be anticipated to increase with playing age, 23 it may be expected that performance in sport-related tasks would too. This may explain why larger SLCMJ asymmetries were associated with better performances in the CODS test (representing sport-specific movement patterns) and the SLCMJ D (representative of neuromuscular capacity on the lunging leg), badminton players have adapted to perform these types of task.…”
Section: Discussionmentioning
confidence: 99%
“…For example, thicker and wider Achilles and patellar tendons in the racket leg. 36 As the magnitude of asymmetry would be anticipated to increase with playing age, 23 it may be expected that performance in sport-related tasks would too. This may explain why larger SLCMJ asymmetries were associated with better performances in the CODS test (representing sport-specific movement patterns) and the SLCMJ D (representative of neuromuscular capacity on the lunging leg), badminton players have adapted to perform these types of task.…”
Section: Discussionmentioning
confidence: 99%
“…A study of moderately active individuals examined similar AT stiffness between non-dominant and dominant legs ( Bohm et al, 2015 ). Another study investigated muscle structure and stiffness in lower limbs and observed no difference in MG and LG stiffness and muscle thickness between dominant and non-dominant lower limbs in professional badminton players ( Bravo-Sánchez et al, 2019 ). Similar results were also observed in the AT stiffness of semiprofessional running athletes and the non-athletic general population ( Dirrichs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the tendon is considered an avascular structure, it has been shown to respond to external mechanical loads by altering its biomechanical properties (Young’s modulus) and/or morphological characteristics (thickness and CSA) [ 27 , 32 ]. Present data showed a PT hypertrophic response associated with SLDSe performed in 6s evidenced by the greater tendon thickness with an increase of 21.8 ± 15.0% at the end of the 6 weeks of the intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were always taken with the subjects lying down. The VL and PT were scanned with the subject in a supine position and the knee flexed at 15° (0° corresponding to full extension of the knee) with a pillow underneath [ 27 ]. All images were analyzed with Image analysis software (Image J, 1.47v, National Institute of Health, MD, USA) to measure fascicle length, pennation angle, muscle thickness, and tendon thickness.…”
Section: Methodsmentioning
confidence: 99%